2018
DOI: 10.5336/jtracom.2018-62824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Awareness and Knowledge of Oral Cancer Among Turkish Patients

Abstract: Ağız kanseri, dünya çapında önemli bir sağlık sorunu hâline gelmiştir. Erken teşhis diğer tüm kanser türlerinde olduğu gibi bu kanser tipinde de sağkalım ve morbidite oranını düşürmektedir. Fakat, erken teşhis için halkın ağız kanseri konusunda farkındalığının artmış olmasına bağlı olarak işaret ve semptomlarını bilmesi gerekmektedir. Bu çalışmada, halk arasında ağız kanseri farkındalığını ve bilgisini değerlendirmek amaçlanmıştır. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Çalışma toplam 839 gönüll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Public oral cancer awareness studies in Turkiye reported diverse results. A study at Konya Necmettin Erbakan University reports that only 18.8% of their dental patients have heard about oral cancer [15]. In a similar setting, 14.3% of the dental patients in Rize thought that oral cancerization was not possible [16].…”
Section: Methodsmentioning
confidence: 99%
“…Public oral cancer awareness studies in Turkiye reported diverse results. A study at Konya Necmettin Erbakan University reports that only 18.8% of their dental patients have heard about oral cancer [15]. In a similar setting, 14.3% of the dental patients in Rize thought that oral cancerization was not possible [16].…”
Section: Methodsmentioning
confidence: 99%